2012
DOI: 10.1177/0266242612455008
|View full text |Cite
|
Sign up to set email alerts
|

The use and impacts of bank support on UK small and medium-sized enterprises

Abstract: This article examines an under-investigated area in relationship banking, i.e. the use of bank advice and support and its impacts on the financial conditions of small and medium-sized enterprises (SMEs). The findings indicate that the characteristics of businesses and entrepreneurs, among other factors, have determinant effects on the use of bank support by SMEs when they make financial decisions. SMEs can alleviate the severity of their financial problems significantly by using bank support more fully, throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
0
12
0
2
Order By: Relevance
“…In this way, relational banking may increase small firms' access to bank facilities or, at least, lead to better terms of contract. For instance, in a study of the effect of bank provided business advice on the financial condition of small firms, Han et al (2012) found that better relationships with banks lowered the entrepreneur's perceptions of difficulties in accessing finance. In line with this, we speculate that applying to a firm's main bank will lower perceived risk for both the entrepreneur and the bank.…”
Section: Independent Variablesmentioning
confidence: 99%
“…In this way, relational banking may increase small firms' access to bank facilities or, at least, lead to better terms of contract. For instance, in a study of the effect of bank provided business advice on the financial condition of small firms, Han et al (2012) found that better relationships with banks lowered the entrepreneur's perceptions of difficulties in accessing finance. In line with this, we speculate that applying to a firm's main bank will lower perceived risk for both the entrepreneur and the bank.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Moreover, Hoshi et al (1990), Grunert andWeber (2009), Shimizu (2012), Gambini and Zazzaro (2013), and Han et al (2014) show the possibility that close firm-bank relationships improve business performance and prevent firms from going bankrupt. 2 For further details, see the ''Appendix''.…”
Section: Introductionmentioning
confidence: 99%
“…On the eve of the World War I, residents' deposits in British banks totaled almost £1.2 billion, with a total bank-note circulation of only £45.5 million (Ferguson 2009). UK SME finance was left predominantly to the big four modern banks-Barclays PLC , HSBC Holdings PLC, Lloyds Banking Group PLC, and Royal Bank of Scotland Group PLC-who still hold 78% of the SME market and 95 percent in the case of Scotland (Han et al 2012).…”
Section: Development Of Financial Institutionsmentioning
confidence: 99%